2018
DOI: 10.1177/1468087417750937
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of automobile N2O from bag and continuous stream by quantum cascade laser spectroscopy

Abstract: N 2 O emission from automobile has been regulated by the United States Environment Protection Agency due to its higher global warming potential compared to CO 2. Responding to this, an instrument for fast sensing of ultra-low concentration of N 2 O from automobile has become an urgent need. In this study, an instrument based on the quantum cascade laser spectroscopy has been developed and applied for certification testing of ultra-low N 2 O in automobile exhaust. The pulsed quantum cascade laser can emit coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The reason is that the three peaks are mainly the active component Cu -BTC peak, and in the catalytic reaction, the characteristic peak of the active component reacts with NH 3 or NO, causing the peak to weaken or even disappear. When SO 2 is introduced, compared with the infrared spectrum of Cu-BTC/FA after denitration, there are almost no new peaks, and the peak shapes are basically similar, which further proves that the sulfur resistance is good [31]. This can be well combined with XRD to explain its denitration mechanism.…”
Section: Ftirmentioning
confidence: 70%
“…The reason is that the three peaks are mainly the active component Cu -BTC peak, and in the catalytic reaction, the characteristic peak of the active component reacts with NH 3 or NO, causing the peak to weaken or even disappear. When SO 2 is introduced, compared with the infrared spectrum of Cu-BTC/FA after denitration, there are almost no new peaks, and the peak shapes are basically similar, which further proves that the sulfur resistance is good [31]. This can be well combined with XRD to explain its denitration mechanism.…”
Section: Ftirmentioning
confidence: 70%
“…Only Mn is loaded, the catalyst does not show the diffraction peak of manganese, indicating that the manganese oxide is evenly distributed on the surface of the catalyst, and the manganese mainly exists in the form of amorphous. The active 35] The rest of the diffraction peaks are obviously broadened, which indicates that Ce will reduce the degree of crystallization of the catalyst and promote the conversion of the active components in the catalyst from the crystalline phase to the amorphous phase, which is very beneficial to the catalytic reaction. MnÀ Ce/FA catalyst before and after reaction showed that the solid solution of MnÀ Ce structure disappeared, which indicated that the MnÀ Ce solid solution was the active substance of the catalyst mainly involved in the reaction.…”
Section: Xrdmentioning
confidence: 99%
“…A large amount of slag is produced every year. Without proper treatment, the residual products occupy a large amount of high-quality land resources, which will not only cause environmental pollution, but also cause serious waste of resources (Rahman et al, 2019;Selvamani et al, 2017). However, because the current slag is mainly based on the preparation of cement or vitreous, it is a waste of resources for the slag to be rich in elements.…”
Section: Introductionmentioning
confidence: 99%